Essays in macroeconomic econometrics - Bejan, Vladimir (Kansas State University, 2012)
This dissertation consists of three essays in macroeconomic econometrics. The first essay investigates industry level production functions. Part of the interest in doing this is to contribute to the ongoing improvements in dynamic macroeconomic models which are increasingly disaggregating economies into industrial sectors. This paper provides useful production function parameter values for this endeavour. In addition, the paper shows that there are differences across industry level production functions, so model disaggregation cannot rely on a generic scaled down aggregate production function. Futhermore, evidence of these differences is provided in several ways. First, it is shown that some, but not all, industry level production functions exhibit constant returns to scale. Second, conducted pairwise tests show whether government capital production elasticities are the same for different pairs of industries. In the majority of these tests, the null hypothesis was rejected. In the second essay, the relevance of wage rigidities for understanding the effect of oil price shocks on output and inflation is examined. The theoretical framework of Blanchard and Gali (2007) is adopted and modified in two important ways. First, an empirically estimated wage adjustment cost function is incorporated following work by Kim and Ruge-Murcia (2009). Second, a realistic monetary policy function is incorporated into the model to be consistent with the current macroeconomic literature. The paper provides evidence that the degree of wage stickiness has little effect on the oil price-macroeconomy relationship. We find that the only way to generate large changes in the variances of output and inflation is to increase the wage adjustment cost by an extreme amount. The third essay assesses the statistical adequacy of the Cobb-Douglas aggregate production function with public capital as an input. The paper tests the statistical adequacy of the models proposed by Aschauer (1989a) and Tatom (1991) and finds that both models are misspecified. Furthermore, the paper finds that Tatom's model suffers from the same criticism he levels against Aschauer's model, non-stationarity in the data series used to estimate the model. Using Aschauer's framework, a properly specified model is found that models both deterministic heterogeneity and serial autocoreelation. Model results find that public capital is positive and significant. The results are in contrast to a large body of literature that discredits Aschauer's findings claiming his model is incorrect. Finally, an additional specification of the model using the student's t linear regression model is explored to capture potential heteroskedasticity.
Keywords: Macroeconomics; Economics (0501)